Textural and compositional variation of sand along the Manahara-Bagmati river basin, Kathmandu Valley - Tamrakar, Naresh Kazi; Gurmaita, Hari Nandan (Journal of Nepal Geological Society, 2001)
The Manahara-Bagmati river basin is located in a humid climate and has a 51 km long low gradient profile. It collects sediments from metamorphic, metasedimentary, and fluvio-lacustrine sources. The sediment samples collected from 17 localities were studied texturally and compositionally to infer how sediment modifies due course of transport and whether the trends are interfered by mixing, recycling, and weathering. For this purpose, two size grades (i.e., 0-1ϕ and 2-3ϕ) were studied. Between them, the trends were more conspicuous in the 0-1ϕ sand grade. Mean (M2) and median (M6) grain sizes increase downstream exponentially. Sorting (σ1) also improves along the river course. Quartz content gradually increases downstream, whilst feldspars and rock fragments decrease remarkably along the river course. Rapid dilution of feldspars and rock fragments (from coarser size grade) occurs after 27 km of transport. The Modified Maturity Index, which ranges from 19.8 to 214, increases from the Manahara to Bagmati River sands. The mica content in the Bagmati River is from 2 to 8 times higher than in the Manahara River. Within the studied river course, the mean projection sphericity (ψp) of quartz remains high (0.80 in average) but does not show any consistent trend. The mean roundness (ρ) of the 0-1ϕ sand grade increases conspicuously against the distance of transport. The majority of samples belong to submature class. Local influx of sediments and recycling are profound from Sankhu to Sanothimi and from Chobhar to Hasdol. Rapid weathering of labile grains is inferred in the middle reach of the Manahara- Bagmati river system (i.e., between Sanothimi and Chobhar).